Effects of rapid maxillary expansion and mandibular advancement on upper airways in Marfan’s syndrome children: a home sleep study and cephalometric evaluation - Taddei, M.; Alkhamis, N.; Tagariello, T.; D’Alessandro, G.; Mariucci, E. M.; Piana, G. (Sleep & breathing, 2015)
Purpose Evaluation of the effects of rapid maxillary expansion and mandibular advancement using Propulsor Universal Light appliance on the upper airways in Marfan’s syndrome children through home sleep studies, Epworth Sleepiness Scale questionnaire, and cephalometric analysis of the upper airways on lateral radiographs. Methods The study sample consisted of 30 children with Marfan’s syndrome, and the control group consisted of 30 untreated and matched children. For Marfan subjects, data were taken at different time points compared to treatment: at T0 (before treatment), T1 (after rapid maxillary expansion), and T2 (after mandibular advancement). For control subjects, data were taken at similar intervals, at three follow-up visits: at T0 (as a starting screening tool), T1 (after approximately 2 years), and T2 (in proximity of the peak skeletal growth). Results Apnea-hypopnea and oxygen desaturations were significantly higher in the study group at T0 and T1 compared with control children. At T2, the values were not significant ( p value 0.442 for both apnea-hypopnea index (AHI) and oxygen desaturation index (ODI)). Horizontal airway dimensions were significantly reduced, and vertical airway values were significantly increased in Marfan’s syndrome at T0 and T1 but not at T2 ( p values at T2: 0.071 for Phw1-Psp, 0.106 for Phw1-Psp’, 0.101 for Phw2-Tb, 0.559 for UAL in male and 0.560 for UAL in female). Conclusions Early rapid maxillary expansion and mandibular advancement using Propulsor Universal Light appliance significantly improved airway patency of Marfan’s syndrome children and are strongly encouraged as a routine treatment for both correction of class II malocclusions and prevention of obstructive sleep apnea.